Prevalence of Dengue fever and dengue hemorrhagic fever in Hospital Tengku Ampuan Rahimah, Klang, Selangor, Malaysia - Jamaiah, I.; Rohela, M.; Nissapatorn, V.; Maizatulhikma, M.M.; Norazlinda, R.; Syaheerah, H.; Tan, H.P. (2005)
Dengue fever and dengue hemorrhagic fever have been known to be endemic and reportable diseases in Malaysia since 1971. Major outbreaks occurred in 1973, 1982 and in 1998. For the past few decades until now. many studies have been performed to investigate the importance of these two diseases in Malaysia. A retrospective study was carried out in Hospital Tengku Ampuan Rahimah Klang to find the prevalence of these diseases. The data was collected from the record department of this hospital starting from the year 1999 until 2003 (5 years). A total of 6,577 cases of dengue fever and 857 cases of dengue hemorrhagic fever were reported. From the year 2000 onwards, cases of dengue fever had increased tremendously. However for the year 2001, there was a slight decrease in the reported cases. Most cases occurred in 2003, increasing from 674 in 1999 to 2,813 in 2003. Highest incidence was seen in Malay males more than 12 years of age. However, the cases of dengue hemorrhagic fever declined tremendously throughout the years. Most cases occurred in 1999 with 674 cases, then declining to only one in the year 2001 before it increased to 60 and 72 in the years 2002 and 2003, respectively. Most cases occurred in patients above 12 years old, the majority of which were Malay males.